Developing a Model of Team Skill Decay. (September 2017) - Fausset, Cara Bailey; Cheng, Samuel; Trani, Alexandra N.; Hutto, Clayton J.; Hale, Chris R.; McDermott, Tom; Nadolski, Molly; Folds, Dennis J.
Predicting team skill decay can support decisions intended to counter erosion of U.S. industrial base essential design skills. Despite the large extant research investigating both individual and team skill acquisition, there is no comprehensive model of skill decay involving intact teams (Day et al., 2013). We conducted a literature review and identified retention interval, initial skill level, task, environment, and team as the critical factors in determining team skill decay. Sub-factors for each critical variable were also specified. A model incorporating each factor is proposed, and in a related research effort (Trani et al., 2017), initial results of applying the model to industry-wide skill decay prediction is presented. Being able to predict and estimate team skill decay supports long-term planning and assessment in all types of industry—from military systems relevant to the industrial base to specific fields such as aviation and healthcare.